Estimation of pre-dolomitisation porosity and permeability of a nummulitic carbonate reservoir rock using the Multi-Component Architecture Method (MCAM). (October 2021) - Mangione, A.; Lewis, H.; Geiger, S.; Jiang, Z.; Couples, G.D.; Buckman, J.; Beavington-Penney, S.; Hall, S.A.
Abstract: The fossiliferous Eocene carbonate reservoir interval of the offshore Hasdrubal Field has a diagenetic history in which dolomitisation of micrite-rich facies has significantly enhanced reservoir quality. Using published information on the diagenetic evolution, digital textural representations of the limestones and dolostones are created using the Multi-Component Architecture Method (MCAM). This technique allows integration of images at different length scales (e.g., SEM, micro-/nano- XRT) which provide different forms of information about the pre-dolomitisation rock, including textural and compositional factors, and the arrangements of preserved components. These digital representations of the dolostones, together with their now completely overprinted precursor micritic limestones, permit exploration of the impact on porosity and permeability of uncemented, partly cemented and biomoulds Nummulites, their number per unit volume, and their orientation (i.e., uniformly or randomly orientated) allowing investigation of the petrophysical consequences of different distributions, orientations and abundances of the matrix and fossiliferous components. Viable diagenetic pathways, which were identified by thin section analysis as well as data available in the literature, are linked to petrophysical property evolution. In this way MCAM permits investigation of earlier stages of the diagenetic processes which were overprinted by later diagenetic processes. Highlights: Create diagenetic stages now overprinted by dolomitisation Digitally generate pore networks to calculate porosity and permeability Micrite, dolomite, Nummulites controls on petrophysics are investigated